Research in the history of economic thought and methodology : Including a Symposium on Latin American Monetary Thought : Two Centuries in Search of Originality - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology, 2019)
In addition to general research contributions, volume 36C features a symposium edited by Andrés Álvarez on monetary economics in post-independence Latin America. The symposium features contributions from Matías Vernengo and Esteban Pérez Caldentey, Ricardo Solis Rosales, Florencia Sember, and Edna Carolina Sastoque Ramírez.